2001
DOI: 10.1007/s004180100260
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of NuMA and phosphorylated proteins during the cell cycle in human breast and prostate cancer cells as analyzed by immunofluorescence and postembedding immunoelectron microscopy

Abstract: The formation of mitotic centrosomes is a complex process in which a number of cellular proteins translocate to mitotic poles and play a critical role in the organization of the mitotic apparatus. The 238-kDa nuclear mitotic apparatus protein NuMA is one of the important proteins that plays a significant role in this process. NuMA resides in the nucleus during interphase and becomes transiently associated with mitotic centrosomes after multiple steps of phosphorylations. The role of NuMA in the interphase nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…19 Inaccurate NuMA regulation and atypical NuMA distribution will result in abnormal mitosis 56 and may result in an inability to support normal embryonic development. We have studied NuMA in somatic cells, 57 pig oocytes 18 and intraspecies and interspecies nuclear transfer embryos and have shown that NuMA is contributed to the reconstructed oocyte by the donor cell nucleus. 17 We do not yet know the mechanisms by which NuMA becomes translocated to the spindle poles in cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
“…19 Inaccurate NuMA regulation and atypical NuMA distribution will result in abnormal mitosis 56 and may result in an inability to support normal embryonic development. We have studied NuMA in somatic cells, 57 pig oocytes 18 and intraspecies and interspecies nuclear transfer embryos and have shown that NuMA is contributed to the reconstructed oocyte by the donor cell nucleus. 17 We do not yet know the mechanisms by which NuMA becomes translocated to the spindle poles in cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
“…As nuclear matrix protein NuMA is involved in DNA replication and transcription. It displays distinct staining patterns in the nucleus (Merdes and Cleveland 1998 ; Zeng 2000 ; Gobert et al 2001 ) and stains heavily in mitosis when using anti-NuMA antibodies (Saredi et al 1997 ; Merdes et al 2000 ; Gobert et al 2001 ; Zhong et al 2005 ; Liu et al 2006 ). Inaccurate NuMA regulation and atypical NuMA distribution will result in abnormal mitosis as has been reported for cancer cells (Saunders et al 2000 ).…”
Section: Centrosome Maturation Into Mitotic Centrosomesmentioning
confidence: 99%
“…Several proteins which are misfolded or overexpressed have been described, especially in neurodegenerative disorders and many types of cancers. Examples include cystatin C in susceptible neurons in Alzheimer's disease (11), NuMA which is an important protein for the formation of mitotic centrosomes (12), and CHMP1 which is a nuclear matrix protein affecting chromatin structure and cell cycle progression (13). Overexpression of the NABC1 protein in cancer cells results in detergent-stable homodimers that leads to punctate localization in cultured cells (14).…”
Section: Discussionmentioning
confidence: 99%